Diagnosis of chronic brucellar meningitis and meningoencephalitis: the results of the Istanbul‐2 study. (4th December 2012) - Erdem, H.; Kilic, S.; Sener, B.; Acikel, C.; Alp, E.; Karahocagil, M.; Yetkin, F.; Inan, A.; Kecik‐Bosnak, V.; Gul, H. C.; Tekin‐Koruk, S.; Ceran, N.; et al.
Abstract No detailed data exist in the literature on the accurate diagnosis of chronic brucellar meningitis or meningoencephalitis. A multicentre retrospective chart review was performed at 19 health centres to determine sensitivities of the diagnostic tests. This study included 177 patients. The mean values of CSF biochemical test results were as follows: CSF protein, 330.64 ± 493.28 mg/dL; CSF/ blood‐glucose ratio, 0.35 ± 0.16; CSF sodium, 140.61 ± 8.14 mMt; CSF leucocyte count, 215.99 ± 306.87. The sensitivities of the tests were as follows: serum standard tube agglutination (STA), 94%; cerebrospinal fluid (CSF) STA, 78%; serum Rose Bengal test (RBT), 96%; CSF RBT, 71%; automated blood culture, 37%; automated CSF culture, 25%; conventional CSF culture, 9%. The clinician should use every possible means to diagnose chronic neurobrucellosis. The high seropositivitiy in brucellar blood tests must facilitate the use of blood serology. Although STA should be preferred over RBT in CSF in probable neurobrucellosis other than the acute form of the disease, RBT is not as weak as expected. Moreover, automated culture systems should be applied when CSF culture is needed.